H5N1 influenza viruses: Facts, not fear - Palese, Peter (National Academy of Sciences, 2012)
The ongoing controversy over publication of two studies involving the transmission in ferrets of H5N1 (H5) subtype influenza viruses and the recommendations of the National Science Advisory Board for Biosecurity to redact key details in the manuscripts call for an examination of relevant scientific facts. In addition, there are calls in the media to destroy the viruses, curtail future research in this area, and protect the public from such “frightening” research efforts. Fear needs to be put to rest with solid science and not speculation.